A geochemical and stable isotope study of some rocks from the Bandelierkop formation, southern marginal zone of the Limpopo Belt, South Africa( vol.1 Text) - Vennemann, Torsten Walter (Department of Geological Sciences, 2017)
The Bandelierkop Formation of the Southern Marginal Zone (SMZ) of the Limpopo Belt consists of metamorphosed ultramafic, mafic and sedimentary rocks. Metamorphic conditions indicated by the petrography of these different rock groups are consistent with upper amphibolite to granulite facies. The ultramafic and mafic rocks are geochemically akin to peridotitic-pyroxenitic intrusive rocks and high-Mg basalts respectively. Metamorphism of these two rock groups in the SMZ was an essentially closed system process, except for the highly volatile phases such as H₂O and CO₂. The metasediments appear to represent a sequence of high (Mg+Fe)-greywackes and/or deep-water shales with minor amounts of iron formation material. The unusually mafic character of the metasediments can be ascribed to a high ultramafic + mafic source component to the original sediment. Some modification of the major and trace element compositions of the pelitic rocks has been caused by the removal of partial melts and the metamorphism of the pelitic rocks is not therefore considered to have occurred under closed system conditions. Variable extraction of partial melts is implied by the chemical variations shown by the pelitic rocks and is also suggested by the presence of large pegmatitic felsic bodies which are commonly found close to the pelitic rocks. Detailed petrographic study of the Bandelierkop Formation rocks suggests an increase in metamorphic grade, and/or a decrease in water activity, from south to north within the Southern Marginal Zone. Peak metamorphic conditions of 730°C + 65°C at pressures of 6.1 ± 1.5 kbars may be deduced from a careful application of several cation thermometers and barometers on selected mineral analyses. A rigorous application of garnet-biotite thermometry to the pelitic rocks indicates that the transition from orthoamphibole gneisses in the south to orthopyroxene-bearing rocks in the north of the SMZ terrane, is a function of changing biotite composition and/or decreasing water activities rather than an increase in metamorphic temperatures. In contrast to the major and trace element data, the stable isotope data for the ultramafic and mafic rocks in the SMZ indicate open system behaviour for some of these rocks, but closed system behaviour for the pelites. Extraction of SO to 70% partial melts from the pelitic rocks, should not, however, have affected the δ¹⁸O value of the restite. Petrological and stable isotope data in the SMZ rocks are consistent with retrogression in all these rocks and open system behaviour for oxygen in some ultramafic and mafic rocks, being caused by the crystallization and accompanying fluid release of melts produced during prograde metamorphism of the pelitic rocks. Small scale (-5 to 30m's) heterogeneity is implied by both oxygen and carbon stable isotope compositions of closely spaced rock samples, even for those collected from within large "shear zones", suggesting small fluid/rock ratios for most of the samples in the high-grade terrane or heterogeneous stable isotopic compositions of the fluids. Furthermore, a similarity in mineral-mineral stable isotope fractionation factors is observed for all the pelitic rocks, including the orthoamphibole gneisses found immediately south of the orthopyroxene isograd. These features preclude the presence of pervasive fluid infiltration after peak metamorphism. Two implications are, that granulite facies metamorphism in the SMZ terrane was not caused by an influx of mantle derived CO₂-rich fluid and, that the orthoamphibole gneisses are not retrogressed equivalents of the granulites found to the north of the orthopyroxene isograd. It is suggested that this isograd represents a change in the water activities of the rocks during metamorphism. Apparent disequilibria in mineral - mineral stable isotope fractionations observed amongst different minerals within any one pelitic rock, may be explained by a combination of the crystallization of residual melt within these rocks and oxygen diffusion amongst minerals which have not reached their oxygen-closure. The concordant quartz-plagioclase, quartz-biotite and plagioclase-biotite oxygen isotope equilibration temperatures are taken to represent minimum crystallization temperatures for the melts (-560°C), while successively higher quartz-orthopyroxene, quartz-amphibole and quartz-garnet oxygen isotope equilibration temperatures are a function of increasing closure temperatures for the orthopyroxene, amphibole and garnet respectively. The minimum estimate to peak metamorphic temperatures is given by the quartz-garnet oxygen isotope temperature averaging 736 + 52°C. If oxygen diffusion experiments performed in hydrothermal systems are appropriate for the SMZ rocks, then cooling rates for the SMZ terrane could have been as low as 12 to 25°C/My over a temperature range of 480 to 600°C. Stable isotope modeling of hypothetical fluids that may have been in equilibrium with the high-grade rocks, suggests that a mixture of CO₂ and H₂O, with CO₂/H₂O mole ratios > 0.1 can precipitate both quartz and carbonate of stable isotope composition similar to those determined for quartz and carbonate from the mineralized Archaean lode gold deposits of the Murchison and Pietersburg greenstone belts. A model involving granulite facies metamorphism, partial melt extraction and subsequent release of fluids, Au, K and S upon crystallization of such melts, appears to be viable for gold mineralization occuring in the adjacent lower grade greenstone belts and in the high-grade terrane of the Southern Marginal Zone.